Correlation of Water Quality Against Prevalence of Ectoparasites in Tilapia (Oreochromis niloticus) in the Floating Net Cages Urban Farming Program in Surabaya, East Java - Cintia Larasati; Gunanti Mahasri; Kusnoto kusnoto (Universitas Airlangga, 2020)
The main obstacle to the cultivation of tilapia (Oreochromis niloticus) in the KJA Urban Farming Program in Surabaya is unstable water quality. This is because the reservoirs and bozem used are waters whose water quality depends on the water source so that if the environment experiences a decrease in water quality, the activity of disease agents such as parasites will increase and the health condition of fish will decrease. This condition allows fish to be more susceptible to ectoparasite infestations. This study aims to determine the correlation of water quality with the prevalence of ectoparasites in tilapia in the KJA Urban Farming Program in Surabaya. The method used is a survey method. The results of measurements of water quality parameters indicate that the temperature ranges between 29-30C, pH 7-8.5, brightness 18-30 cm, dissolved oxygen 4.8-5.3 mg / l, nitrite <0.043-2.213 mg / l, nitrate <0.008-7.781 mg / l and ammonia 0.063-0.35 mg / l. The results of the average prevalence of Trichodina ectoparasites were 73.85% and Dactylogyrus ectoparasites were 2.85%. There is a positive correlation between temperature, pH, nitrate, nitrite with the prevalence of Trichodina, and temperature, pH, and nitrate with the prevalence of Dactylogyrus. There is a negative correlation between brightness, dissolved oxygen and ammonia with the prevalence of Trichodina, and brightness, nitrite, dissolved oxygen, and ammonia with the prevalence of Dactylogyrus.